Potentialities and constraints on the fundamental rights: a comparative approach / Noor Mohammad - Mohammad, Noor (2014)
Fundametal rights are the constitutional rights that can never be denied under any circumstances as pointed out in the most of the constitutions in the world. In fact, these rights can never be restricted by any laws and policies as guaranteed in the constitutions. These rights are more liberal in the developed countries as compared to developing as well as the middle east countries. For example, Bangladesh, Malaysia, Saudia Arabia, Bahrain etc; they have some laws that restricted their fundamental liberities to some extent. The prevention of Crimes Act, 2013; the Special powers Act, 1974; the Sedition Act;1948 etc; are notable. However, this study intends to assess the potentialities and constraints on the fundamental liberies under the different constitutional laws focusing on Malaysia, Bangladesh consisting of at least 25 respondents based on the primary and secondary sources at UKM.